2007
DOI: 10.1002/psc.923
|View full text |Cite
|
Sign up to set email alerts
|

Conformational studies of alanine‐rich peptide using CD and FTIR spectroscopy

Abstract: The circular dichroism (CD) and Fourier transform infrared (FTIR) methods were applied to the conformational studies of alanine-rich peptide Ac-K-[A]11-KGGY-NH2 (where K is lysine, A is alanine, G is glycine and Y is tyrozyne) in water, methanol (MeOH) and trifluoroethanol (TFE). The analysis of CD-spectra of the peptide in water at different concentrations revealed that the secondary structure content depends on the peptide concentration and pH of the solution. The increase of the peptide concentration causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 42 publications
2
75
0
Order By: Relevance
“…The FT-IR spectroscopy is complementary to the CDspectroscopy method according to the conformational studies of peptides and proteins (Bagińska et al, 2008). Therefore, sometimes they may be used simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…The FT-IR spectroscopy is complementary to the CDspectroscopy method according to the conformational studies of peptides and proteins (Bagińska et al, 2008). Therefore, sometimes they may be used simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…The PEG‐PA was synthesized by the ring‐opening polymerization of the N ‐carboxy anhydrides of l‐alanine, where α‐amino‐ω‐methoxy PEG was used as an initiator . The α‐amino‐ω‐methoxy PEG (5.0 g, 5.0 mmole) was dissolved in anhydrous toluene (70 mL) and the residual water was removed by azeotropic distillation to a final volume of about 10 mL.…”
Section: Methodsmentioning
confidence: 99%
“…For example, CD spectral analysis of alanine-rich peptide Ac-K-[A] 11 -KGGY-NH 2 demonstrated that the α-helix content of the self-assembled peptide depended on peptide concentration in water and secondary structure was independent of temperature (76). FTIR spectra of the same peptide in water revealed that the β-sheet structure dominated at higher concentrations (76). The interaction of the polymer chain with conjugated peptide can be studied by X-ray reflectivity as well as CD and FTIR (77,78).…”
Section: Characterization Of Peptidomimetic Npsmentioning
confidence: 99%
“…The secondary structure of the synthesized peptide and peptide-polymer conjugate can be characterized by circular dichroism (CD) and Fourier Transform Infrared Spectrometry (FTIR) (76). CD and FTIR spectral range of 200-300 nm and 1,500-1,800 cm −1 , respectively, are utilized for analysis of secondary structures (76).…”
Section: Characterization Of Peptidomimetic Npsmentioning
confidence: 99%
See 1 more Smart Citation